Improving the Competitiveness of the Manufactured Product (Texas Journal of Multidisciplinary Studies, 2022)
The article says that the leadership of Uzbekistan pays special attention to changes in the agricultural sector, at the same time, along with the peculiarities of the agrarian sphere of our country and the traditions that have developed in it, the experience of foreign countries, including the experience of the armies of the CIS member countries, is noted, having studied them in this way, we want to offer them a new experience of conducting the results and getting to know some of their problems.